PELESTARIAN SUBAK MELALUI PEMBERDAYAAN ANGGOTANYA DALAM PEMBUATAN PAKAN TERNAK SAPI BALI ALTERNATIF KOMBINASI JERAMI PADI DAN BATANG PISANG SECARA FERMENTASI - I. N. Simpen; I. M. Sutha Negara; N.G.A.M. Dwi Adhi S.; M. Arsa; N.L. Arpiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The activity in Subak Dangin Alas Desa Lodtunduh Ubud, to be aim for producing woof of bali cattlealternative by fermentation of mixture banana culm and rice straw which has been carried out from May toSeptember. The activity of subscribers of subak sustainability and continuesly, it is expected to impact onmaintenance of the subak in its village. In this activity, have been done survey, producing of cattle woofalternative, socialized, training, accompanying and giving woof to their cattles. In producing of woof of balicattle, it was done by cutting byproduct of banana culm and rice straw to be size 3-5 cm, then dried 1-2 daysfor reducing water content and then the fermentor (active microorganism and molasses) and mixture of riceand bran are distributed on its byproduct. The final step, it has been done fermentation for minimum 7 days.The activity result, subscribers of subak were very anthusiastic. Generally, participants have yet tounderstand detail procedure to make cattle woof alternative which is healthful, natural and preserve byfermentation, so that the application of technology is useful. The cattles may consume its fermentationproduct.